2000
DOI: 10.1046/j.1464-5491.2000.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of screening and monitoring tests for diabetic retinopathy – a systematic review

Abstract: Based on an assessment of available cohort studies, the most effective strategy for testing is the use of mydriatic retinal photography with the additional use of ophthalmoscopy for cases where photographs are ungradable. This does not exclude the use of ophthalmoscopy alone for opportunistic case finding but there is evidence of considerable variation in effectiveness of this test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
153
2
9

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 26 publications
4
153
2
9
Order By: Relevance
“…Simulation models suggest that substantial savings, both monetary and in sight-years, are reached with an overall sensitivity of 60%, as the cost-benefit curves drop steeply for lower sensitivities and plateau for better performances [65]. Since average sensitivity and specificity for trained operators and dedicated equipment range from 80 to 90% [66], available methodologies could be deployed with very good prospects of success. A recent systematic review concluded that mydriatic retinal photography, associated with direct and/or indirect ophthalmoscopy if the pictures are ungradable, remains the most reliable screening test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation models suggest that substantial savings, both monetary and in sight-years, are reached with an overall sensitivity of 60%, as the cost-benefit curves drop steeply for lower sensitivities and plateau for better performances [65]. Since average sensitivity and specificity for trained operators and dedicated equipment range from 80 to 90% [66], available methodologies could be deployed with very good prospects of success. A recent systematic review concluded that mydriatic retinal photography, associated with direct and/or indirect ophthalmoscopy if the pictures are ungradable, remains the most reliable screening test.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review concluded that mydriatic retinal photography, associated with direct and/or indirect ophthalmoscopy if the pictures are ungradable, remains the most reliable screening test. [66]. FAG should not be used to screen.…”
Section: Methodsmentioning
confidence: 99%
“…Studies comparing methodologies for diagnosis of diabetic retinopathy are lacking in dogs, but it is reasonable to assume that ophthalmoscopy alone may miss subtle lesions. Although ophthalmoscopy is accepted as the most commonly used screening tool for diabetic retinopathy in humans, fluorescein angiography and multiple field stereoscopic fundus photography are more sensitive than ophthalmoscopy alone in detecting the condition 32, 33. However, neither multiple field stereo fundus photography nor fluorescein angiography is practical to employ on a routine basis with clinical veterinary patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that mydriatic retinal photography provides the most effective screening and monitoring test for detection of sight-threatening diabetic retinopathy. 6 In general, the sensitivity and specificity levels were higher in studies where retinal photography was the method of choice.…”
Section: Introductionmentioning
confidence: 96%
“…The Diabetes Control and Complications Trial highlighted the importance in insulin-dependent diabetes mellitus (IDDM) of good diabetic control in reducing the risk of progression of retinopathy. 6 Similarly, the UKPDS demonstrated that good control of both blood pressure and diabetes in type II diabetics significantly reduced the risk of microvascular end points related to diabetes including retinopathy. 7 The benefits of laser photocoagulation are well known.…”
Section: Introductionmentioning
confidence: 98%